2021
DOI: 10.1111/jmft.12522
|View full text |Cite
|
Sign up to set email alerts
|

Past is present: Pathways between childhood sexual abuse and relationship satisfaction

Abstract: Research on childhood sexual abuse (CSA) has consistently demonstrated the damaging effects of these experiences, not only on survivors' development, but also on the nature and quality of their adult relationships, particularly romantic ones. Yet, research to date has not demonstrated a strong direct effect of CSA on relationship satisfaction. This study examined the pathways from CSA to relationship satisfaction via sexual shame and romantic partner attachment. Data collected through surveys from 732 adults w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 59 publications
0
3
1
Order By: Relevance
“…As for the moderating role of childhood abuse, we found interesting results. While the vast majority of research on childhood abuse and adult intimate relationships has emphasized outcomes among survivors of childhood sexual abuse (Barker et al, 2021; Davis & Petretic-Jackson, 2000), the current study found moderating effects for physical and emotional abuse, but not for sexual abuse. Specifically, concern caregiving exerts a greater effect on intimacy among participants who had experienced low levels of physical abuse or high levels of emotional abuse.…”
Section: Discussioncontrasting
confidence: 66%
“…As for the moderating role of childhood abuse, we found interesting results. While the vast majority of research on childhood abuse and adult intimate relationships has emphasized outcomes among survivors of childhood sexual abuse (Barker et al, 2021; Davis & Petretic-Jackson, 2000), the current study found moderating effects for physical and emotional abuse, but not for sexual abuse. Specifically, concern caregiving exerts a greater effect on intimacy among participants who had experienced low levels of physical abuse or high levels of emotional abuse.…”
Section: Discussioncontrasting
confidence: 66%
“…Humans are inherently social beings, with social connection, healthy attachments and touch fundamental to our survival and emotional well‐being (Dreisoerner et al., 2021; Harandi et al., 2017; Mikulincer & Shaver, 2016). Sexual trauma has been described as a violation of our intrinsic human connection, dramatically impacting a person's ability to feel safe in relationships (Barker et al., 2022; Yuan, 2022). Therefore, rebuilding trust and a sense of security with others appears vital in the aftermath of sexual abuse.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The adulthood relationships surveys of Barker (2021) demonstrate that the correlation between childhood sexual abuse and relationship satisfaction is negative [1]. However, the definition of CSA age is uncertain.…”
Section: Introductionmentioning
confidence: 99%